2019
DOI: 10.3389/fmicb.2019.01831
|View full text |Cite
|
Sign up to set email alerts
|

Role for Gag-CA Interdomain Linker in Primate Lentiviral Replication

Abstract: Gag proteins underlie retroviral replication by fulfilling numerous functional roles at various stages during viral life cycle. Out of the four mature proteins, Gag-capsid (CA) is a major component of viral particles, and has been most well studied biogenetically, biochemically and structurally. Gag-CA is composed of two structured domains, and also of a short stretch of disordered and flexible interdomain linker. While the two domains, namely, N-terminal and C-terminal domains (NTD and CTD), have been the cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…It has been previously demonstrated that HIV Pro-147 is part of a disordered linker domain which connects the HIV capsid N-terminal domain (CA-NTD) and the capsid C-terminal domain (CA-CTD) ( 26 , 27 ). Mutations in this domain can result in improper formation of the capsid, leading to a reduction in the number of viable virions produced, and SIV shares a similarly biologically active linker region with HIV ( 28 ). The presence of Thr-146 is presumably an error that arose during PCR and cloning, since bulk sequence analysis of the virus isolate that was the source of the CL757 cloned, SIVsmm804E ( 12 ), showed that this isolate and additional clones from it encoded a Pro at this site (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…It has been previously demonstrated that HIV Pro-147 is part of a disordered linker domain which connects the HIV capsid N-terminal domain (CA-NTD) and the capsid C-terminal domain (CA-CTD) ( 26 , 27 ). Mutations in this domain can result in improper formation of the capsid, leading to a reduction in the number of viable virions produced, and SIV shares a similarly biologically active linker region with HIV ( 28 ). The presence of Thr-146 is presumably an error that arose during PCR and cloning, since bulk sequence analysis of the virus isolate that was the source of the CL757 cloned, SIVsmm804E ( 12 ), showed that this isolate and additional clones from it encoded a Pro at this site (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Mutagenesis studies have been used to confirm the importance of the interface residues for core morphology and stability and virion infectivity (24,25,30,31). Mutations in the CA domain of Gag have been shown to affect particle assembly and virion infectivity in different retroviruses, including HIV-1 (32), Simian immunodeficiency virus (SIV) (33), Mason-Pfizer monkey virus (M-PMV) (34), and RSV (35).…”
Section: Introductionmentioning
confidence: 99%
“…Several key mutants, such as HIV-1 CA W184A and M185A caused Gag assembly defects, produced non-infectious viruses, reduced CA dimerization and intermolecular Gag–Gag interactions in vitro , diminished immature particle production in vivo , and abolished CA dimerization [29, 35]. Moreover, parallel studies have been done on SIVmac constructs [32]. However, there have been no studies focused on HIV-2 critical amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…Mutagenesis studies have been used to confirm the importance of the interface residues for core morphology and stability and virion infectivity (24, 25, 30, 31). Mutations in the CA domain of Gag have been shown to affect particle assembly and virion infectivity in different retroviruses, including HIV-1 (32), Simian immunodeficiency virus (SIV) (33), Mason-Pfizer monkey virus (M-PMV) (34), and RSV (35). Several key mutants, for example the HIV-1 CA W184A and M185A cause Gag assembly defects, produce non-infectious virus particles, reduce CA dimerization and intermolecular Gag–Gag interactions in vitro , diminish immature particle production in vivo , and abolish CA dimerization (30, 36); similar studies have been done with SIV (33).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation